Receptive Vocabulary Size of Omani Post-Basic Education Graduates (Journal of Education and Development, 2023)
This descriptive study examined the receptive vocabulary size of Omani post-basic education graduates. Also, it investigated the relationship between receptive vocabulary size and language proficiency among these students. Finally, it examined differences in receptive vocabulary size with respect to gender. The sample consisted of 294 Omani post-basic education graduates (183 males and 111 females) who were enrolled in foundation programs at Sultan Qaboos University. The study instrument was the Vocabulary Level Test Version B, which was developed by Nation (1983) and revised by Schmitt, Schmitt, and Clapham (2001). The study found that the Omani post-basic graduates had a small receptive vocabulary of approximately 1,725 word families. It also found a statistically significant relationship between students’ receptive vocabulary size and their language proficiency. Finally, it revealed statistically significant differences in receptive vocabulary size with respect to gender in favor of female students. Accordingly, the researcher provides recommendations for practice and further research.